Frequency of Complications Following Laparoscopic Cholecystectomy in Alzahra Teaching Hospital, Isfahan, Iran (2009-2011) - Behrooz Kaleidari; Hassan Dehghan-Banadkuki; Mehdi Khazaei; Shahab Shahabi-Shahmiri (مجله دانشکده پزشکی اصفهان, 2015)
Background: Gallstone is one of the commonly encountered diseases in the general population. Laparoscopic cholecystectomy (LC) is now accepted as the “gold standard” for the treatment of gallstone. The purpose of this study was to present our data about the type and the incidence of complications of laparoscopic cholecystectomy.